المفارقة الدرامية في شعر أدونيس - الحياني، محمود خليف خضير (جامعة ذي قار - كلية الآداب, 2015)
The dramatic irony in Adonis's poetry establishes as a strategy and technique based on sarcasm , irony, puns embodied in the comic event and the tragic act noticed in the obsession of sympathy, the mimic predictive fear or reflection of contradictories and the oppositions legitimated by social, political and cultural reality lying in the dialectical case that carries misleading images and forms more than being real. Adonis's exposure of the dramatic irony takes benefit from the stagy and dramatic technique that depends on the presence of the masked and invisible character and the dramatic style that includes the act of tones and phonetic segmentations that grow and develop the dramatic event and case inversion connected to the interpretive and contextual dimension
اشتغلت المفارقة الدرامية في شعر أدونيس على أساس وصفها استراتيجية، وتقنية قائمة على التهكم والسخرية واللمز المتجسدة في فعل الحدث الكوميدي، والمأساوي المتمظهر في هاجس التعاطف، والتوجس التنبؤي المحاكي أو العاكس للتناقضات والضديات التي شرعنها الواقع الاجتماعي والسياسي والثقافي الثاوي في حالة الجدلية المحملة بصور وأشكال تضليلية أكثر منها واقعية، وإن الكشف الأدونيسي للمفارقة الدرامية قد أفاد من التقنية المسرحية، والدرامية التي اتكأت على حضور الشخصية التنكرية والمخفية واللغة الدرامية التي تنطوي على فعل النبرات، والتقطيعات الصوتية التي نمت وطورت سيرورة الحدث الدرامي، وانقلاب الحال المرتبط بالبعد التداولي والسياقي.
Keywords: المفارقة الدرامية; الشعر العربي; لغة المفارقة الدرامية; التوجس المأساوي